Effect of Zr Content on the Distribution Characteristic of the 14H and 18R LPSO Phases - Zhang,Wanneng (2020)
Abstract Zirconium (Zr) is an essential element in Mg-Zn and Mg-Zn-Y system magnesium alloys. In this study, an interesting phenomenon that the content of Zr element could influence the size and the morphology of the long period stacking ordered (LPSO) phases, which has never been reported by previous works before. The Mg98.5-xZn0.5Y1Zrx (x =0, 0.1, 0.2 and 0.3 at. %) magnesium alloys were fabricated by directional solidification, and the effects of the Zr content on the distribution characteristics of the bulk LPSO phases (18R) and the lamellar LPSO phases (14H) were investigated. The directional solidification technology showed good controllability in LPSO phase’s distribution, and the morphology of LPSO phases in Mg98.5-xZn0.5Y1Zrx (x =0, 0.1, 0.2 and 0.3 at. %) alloys were observed clearly. The results showed that the amount and the morphology of the 14H and 18R LPSO phases within grains continuously decreased with the Zr content increasing. The continuous 14H lamellar structure changed to discontinuous. In addition, Zr element exhibited purification ability on the grain boundaries and refined effect on the 14H and 18R LPSO phases. This can be attributed to the influence of Zr atoms on stacking fault energy (SFE) and the attraction of Zr atoms to Mg atoms.